Mortgage Defaults - Martinez, Leonardo (IMF Working Papers; Working Paper ;, 2012)
This paper incorporates house price risk and mortgages into a standard incomplete market (SIM) model. The model is calibrated to match U.S. data and accounts for non-targeted features of the data such as the distribution of down payments, the life-cycle profile of home ownership, and the mortgage default rate. The average coefficients that measure the agents' ability to self-insure against income shocks are similar to those of a SIM model without housing but housing increases the values of these coefficients for younger agents. The response of consumption to house price shocks is minimal. The introduction of minimum down payments or income garnishment benefits a majority of the population.